PS01.202: MANAGEMENT OF RESECTABLE ESOPHAGEAL AND GASTRIC (MIXED ADENO)NEUROENDOCRINE CARCINOMA: A NATIONWIDE COHORT STUDY. (14th September 2018) - Van Der Veen, A; Seesing, Mfj; Wijnhoven, Bas P L; Steur, Wo; Van Berge Henegouwen, Mark I; Rosman, Camiel; Van Sandick, Johanna; Mook, Stella; Haj Mohammad, Nadia; Hillegersberg, Richard; Ruurda, Jelle; Brosens, Lodewijk
Abstract: Background: Esophageal and gastric neuroendocrine- and mixed adenoneuroendocrine carcinomas (NEC, MANEC) are very rare. Optimal treatment strategies, the role of surgery and outcomes remain unclear. The aim of this study is to provide insight in accuracy of diagnosing, current treatment and survival in patients with resectable esophageal and gastric (MA)NEC. Methods: All patients with esophageal or gastric (MA)NEC, who underwent surgical resection between 2006–2016, were identified from the Dutch national registry for histo- and cytopathology (PALGA). Patients with a neuroendocrine tumor lower than grade 3 were excluded. Data on patients, treatment and outcomes were retrieved from the patients record. Diagnosis by endoscopic biopsy was compared with diagnosis by resection specimen. Kaplan Meier survival analysis was performed. Results: A total of 49 patients were identified in 25 hospitals, including 21 patients with esophageal (MA)NEC and 26 patients with gastric (MA)NEC on resection specimen. Biopsy diagnosis of (MA)NEC was correct in 23/27 patients. However, 20/47 patients with definitive diagnosis of (MA)NEC, were misdiagnosed on biopsy. Neoadjuvant therapy was administered in 13 (62%) esophageal (MA)NECs and 12 (46%) gastric (MA)NECs. Survival curves were similar with and without neoadjuvant therapy. One (4.8%) esophageal (MA)NEC and 4 (15%) gastric (MA)NECs died within 90 days postoperatively. For esophageal (MA)NEC the median overall survival (OS) after surgery was 37 months and 1-, 3- and 5-year OS were 71%, 50% and 35%, respectively. For gastric (MA)NEC, the median OS was 23 months and 1-, 3- and 5-year OS were 62%, 50% and 39%, respectively. Conclusion: Localized esophageal and gastric (MA)NEC are often misdiagnosed on endoscopic biopsies. After resection, long-term survival was achieved in respectively 35% and 39% of patients. Disclosure: All authors have declared no conflicts of interest.